Managment of the materialized representations in information systems - Кунгурцев, Алексей Борисович; Возовиков, Юрий Николаевич (Eastern-European Journal of Enterprise Technologies, 2012)
The method of analysis of materialized representations based on the analysis of dynamic characteristics of information systems. The proposed method allows increasing the effectiveness of MR by MR adjustment depending on changes that occur in information systems.